Happy Hen Heaven: A feasibility study for a free-range poultry farm in Antipolo, Rizal - Constantino, Lorie Mae R., Evaristo, Princess Belinda P., Maranga, Erma G., Ortizano, Mery Kristine B., Tarog, Yves N., Vincente, Ginelle D. 4 0 16; 5
PROJECT STUDY: The Happy Hen Haven is a commercial enterprise situated on a free-range poultry farm. The business is operated by (6) six partners within a Limited Liability Partnership (LLP) framework. This legal structure protects the personal assets of each partner from financial liabilities associated with the economic operations of the firm. Establishing the farm necessitates compliance with several legal requirements and the payment of fees to obtain the necessary licenses and permits. The primary commodity of the farm will be free-range eggs An increasing number of consumers actively seek these eggs. The belief is that these eggs possess higher nutritional content, superior taste, and originate from ethically produced farming practices. Chickens that produce free-range eggs are allowed to free-range outdoors. They roam in search of natural food. Therefore, this results in eggs of superior quality. Furthermore, it aligns with the preferences of consumers: food produced in environmentally friendly and ethically responsible methods. Antipolo, Rizal was selected as the host for the Extraordinary Opportunity for several compelling reassons. Studies indicate that the region has a limited number of officially declared poultry farms, suggesting a potential market void. The presence of numerous poultry farms in certain areas of Rizal contributes to the less saturated market of Antipolo. The favorable climatic conditions in the region, together with its proximity to major urban hubs in Metro Manila, enhance its suitability for chicken farming. Implementing Happy Hen Haven appears to be a very promising entrepreneurial concept. By offering high-quality free-range eggs to consumers, the farm can satisfy the increasing need for sustainable and locally sourced food. Furthermore, its strategic position in Antipolo grants it entry into a lucrative market at a minimal level of completion.
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2